Effects of Mn(II) on nano silicon@polyaniline electrodes in both half and full cells. (11th December 2020) - Chen, Haihui; Xu, Hanying; Zeng, Yingying; Cai, Jinhua; Liu, Limin; Ma, Tianyi; Wang, Fang; Qiu, Xinping
Summary: In situ growing conductive polyaniline (PANi) has been regarded as a functional binder to enhance the performance of silicon based anodes in half cells, while few papers discussing the influence of Mn 2+ from cathode on full cells. In this paper, the effects of Mn 2+ on NSi@PANi electrodes in both half and full cells are investigated, and the mechanism for the fast capacity fade of LiMn2 O4 /NSi@PANi full cell is elucidated. Results reveal that the full cell will significant accelerate the capacity fade of NSi@PANi anode, and the extra consumption of active Li + and electrolytes caused by the deposited Mn 2+ on silicon anodes in lithium manganate (LMO)/NSi@PANi full cells is confirmed as the main reason of the capacity fade and lower coulombic efficiency for the excessive growth of solid electrolyte interphase. Abstract : Extra consumption of active Li+ and electrolytes caused by the deposited Mn2+ on silicon anodes in lithium manganate (LMO)/NSi@PANi full cells is confirmed as the main reason of the capacity fade and lower coulombic efficiency for the excessive growth of solid electrolyte interphase.